KAJIAN PEMETAAN LAHAN PERTANIAN PANGAN BERKELANJUTAN (LP2B) DI KABUPATEN PURWOREJO - Melulosa Andhytya Sakti; Bambang Hendro Sunarminto; Azwar Maas; Didik Indradewa; Bambang Djadmo Kertonegoro (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : Mapping of Food Agricultural Land Sustainability (LP2B) in Purworejo District. Implementation of Act 41 of 2009 on sustainable agricultural land still needs to be improved. Purworejo has a total area of 103,481.75 hectares consisting of rice, dry land and mixed garden. Increased development of a high enough lead Purworejo prone land conversion primarily agricultural to non-agricultural land. Determination of sustainable agricultural land is expected to control the pace of the transfer function. This study aims to determine the parameters for mapping LP2B and LCP2B, determine the basis for assessing inter-parameter calculation and LCP2B LP2B, determine the characteristics of the grouping criteria as LP2B agricultural land and agricultural land mapping LCP2B and sustainable food (LP2B) Purworejo. The data used in this study include spatial data and spatial data tabulated data consists of the Present landuse map the results of high-resolution satellite image interpretation purworejo district scale 1:25,000, topographic maps, maps of land suitability, administration district map boundaries, and maps of raw paddy fields. Tabulation of data consists of the need and availability of food, food balance, wetland conversion, the rate of population growth, and land area requirements. The survey results revealed that the total population, wetland production, planted area, harvested area, conversion rate and balance of food can be used as a parameter to specify the grouping criteria LP2B while land based on the irrigation system and the productivity of more than 5.5 tonnes / ha with IP is more than 1.75. Based on the analysis Purworedjo county has a total area of 38,562 ha area of agri-food consisting of 27,850.18 ha of wetlands and 10,712 ha of dry land. Of the area that became wet LP2B area of 25,826 ha and 5,243 ha of dry LP2B. Sustainable food agriculture land reserve wet (wet LCP2B) 2,024 ha and sustainable agri-food reserves dry (dry LCP2B) 5,469 ha.